Analisis Desain Gerak dalam Media Motion Graphic Pencegahan Covid 19 oleh Kementerian Kesehatan RI - Wahju Tri Widadijo (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2021)
This study reviews the analysis of motion design on motion graphics media. The analysis was carried out on several motion graphic videos about the prevention of Covid 19 by the Indonesian Ministry of Health which were broadcast through the Youtube channel (https://www.youtube.com/c/KementerianKesehatanRI/videos). The analysis process was using a qualitative descriptive method. The fundamental animation motion design principles as developed by Frank Thomas and Ollie Johnston (1981) were used as references to identify, observe, and describe existing motion designs. The fundamental principles are limited to the Squash and Stretch principle, the Anticipation principle, the Follow Through and Overlapping Action principle, the Slow In and Slow Out principle, and the Timing principle. This research is based on the initial assumption, that the more natural the motion design used in motion graphic media, the more attractive and pleasing motion will appear.